Gluten-free bread: a case study - Correia, Paula (2017)
Physicochemical and sensorial characteristics of a possible commercial gluten-free bread (GFB) made with a new gluten-free flour were studied, as compared to a regular wheat bread, which was also analysed as Control sample. Results show that GFB presented high values of moisture and water activity, 36.56% and 0.96. This bread presented high density (0.38 g/ cm3) comparing to regular bread (0.25 g/ cm3), being these results reinforced by image analysis of alveoli. GFB was whiter, with less color intensity, meaning that a* and b* color parameters were lower than control, which was confirmed by sensorial evaluation results. GFB was soft and easily chewable (75.0 N and 70.0 N, respectively for hardness and chewiness), which, once again, was corroborated by the sensorial results. The overall assessment done by the consumer panellist to GFB was 4.1 (on a scale from 1 to 10), while the control bread presented 5.5. It could be concluded that the new flour formulation is suitable for GFB production, with characteristics comparable with the regular bread.